2014
DOI: 10.1016/j.ijnss.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and caveats of international nurse migration

Abstract: a b s t r a c tWorldwide, there is a dramatic shortage of nurses. An increase in the migration of nurses from their home countries to recipient countries is having a global effect on the healthcare system. This global phenomenon stems from historical, economical, social, and political factors. Migration has a significant impact on both the individual and national level. This article summarizes the factors that contribute to nurse migration form the perspective of the source and recipient countries. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 18 publications
2
74
0
3
Order By: Relevance
“…This trend introduces the challenges of transitioning to a new healthcare culture, where nurses can experience high levels of distress requiring a long period of adjustment to the new society (Li et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…This trend introduces the challenges of transitioning to a new healthcare culture, where nurses can experience high levels of distress requiring a long period of adjustment to the new society (Li et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In pharmacy in Great Britain (GB – England, Scotland and Wales), the proportion of internationally trained pharmacists (ITPs) has risen from 10.1% in 2004 to 11.8% in 2011 . While a great deal of research has been undertaken on internationally trained doctors (ITDs) and nurses (ITNs), less is known about ITPs . It is known that internationally trained healthcare professionals, including pharmacists, face numerous challenges in their adaptation process into the host heal the care system .…”
Section: Introductionmentioning
confidence: 99%
“…While a great deal of research has been undertaken on internationally trained doctors (ITDs) and nurses (ITNs), less is known about ITPs . It is known that internationally trained healthcare professionals, including pharmacists, face numerous challenges in their adaptation process into the host heal the care system . Where English is a foreign language, the literature on ITNs and ITDs has identified language and communication barriers as a root cause for issues related to adaptation and integration of these healthcare professionals into the workforce, with some studies raising the potential impact of communication problems on patient safety and quality of care …”
Section: Introductionmentioning
confidence: 99%
“…post migration have concluded that the migration of Filipino nurses is primarily driven by economics (Alonso-Garbayo & Maben, 2009; International Organization for Migration [IOM], 2013;Li, Nie, & Li, 2014;Lorenzo et. al, 2007;Tiongco-Cruda, 2008).…”
Section: Many Academics and Scholars Who Have Explored Filipino Nursementioning
confidence: 99%
“…Africa is now considered to be in a "nursing crisis" characterised by nursing inadequacy, and is plagued by issues of nurse migration from that continent (International Council of Nurses, 2007). For example, in 2002, South Africa had an estimated 30 percent hospital staff vacancy rate due to nursing staff shortages and as a result of nurse migration (Li, Nie, & Li, 2014). In 2010, African countries had one nursing or midwifery personnel per 1,000 population compared to five nursing or midwifery personnel per 1,000 population in America and eight nursing or midwifery personnel per 1,000 in Europe (Naicker, Eastwood, Plange-Rhule, & Tutt, 2010).…”
Section: Global Nurse Migration: a Realitymentioning
confidence: 99%